Operations and Supply Chain Management - Chase, Richard B.; Chase (New York : McGraw Hill, 2016)
Jacobs and Chase continue to lead the field of Operations Management with cutting edge up-to- date content, technology, and motivation. Now, in this First Edition Jacobs and Chase focus on the core concepts of operations and supply management. This condensed text was constructed with the four essential core areas of process, quality, inventory, and supply chain management in mind, as decided by a panel of OM instructor's at the Decision Science Institute meeting, and after conducting a survey of content coverage in representative universities. The new Core text provides increased emphasis on supply management concepts along with a focused presentation of the core OM concepts.